Body mass index status and peripheral airway obstruction in school-age children: a population-based cohort study. Issue 6 (29th January 2018) - Ekström, Sandra; Hallberg, Jenny; Kull, Inger; Protudjer, Jennifer L P; Thunqvist, Per; Bottai, Matteo; Gustafsson, Per Magnus; Bergström, Anna; Melén, Erik
Abstract : Background: Few large prospective studies have investigated the impact of body mass index (BMI) on lung function during childhood. Methods: Using data collected between 2002 and 2013, we analysed associations between BMI status and lung function (assessed by spirometry) from 8 to 16 years, as well as cross-sectional associations with small airway function (impulse oscillometry) at 16 years in the BAMSE cohort (n=2889). At 16 years, cross-sectional associations with local and systemic inflammation were investigated by analysing FENO, blood eosinophils and neutrophils. Results: Overweight and obesity at 8 years were associated with higher FVC, but lower FEV1 /FVC ratio at 8 and 16 years. In boys, but not girls, obesity at 8 years was associated with a further reduction in FEV1 /FVC between 8 and 16 years. In cross-sectional analyses, overweight and obesity were associated with higher frequency dependence of resistance (R5–20 ) and larger area under the reactance curve (AX 0.5 ) at 16 years. Increased blood neutrophil counts were seen in overweight and obese girls, but not in boys. No association was found between BMI status and FENO . Persistent, but not transient, overweight/obesity between 8 and 16 years was associated with higher R5–20 and AX 0.5 and lower FEV1 /FVC (−2.8% (95% CI −4.1 to −1.2) in girls and −2.7% (95% CI −4.4 to −1.1) in boys) at 16 years, compared with persistent normal weight. Conclusion: In childhood and adolescence, overweight and obesity, particularly persistent overweight, were associated with evidence of airway obstruction, including the small airways.